Morality and value neutrality in economics: a dualist view - Cheng Li (Editura ASE Bucuresti, 2019)
This paper proposes a dualist view that economics exhibits the properties of both moral science and value-neutral approach, regardless of the normative-positive distinction. Our argumentation is derived from the understanding that, analytically, economics is a broadly-defined rational choice theory. As implied by this claim, on the one hand, economics behaves as a moral science for two main reasons: all economic theories and policy discussions are necessarily based on moral premises about means-end considerations; economics as an analytical approach can be and has been applied to explanations of a wide range of moral phenomena. On the other hand, since economists — without being informed of some ethical presuppositions of higher order — cannot deal with the comparisons among different value criteria, their approach remains neutral regarding judgmental positions, which should be given a priori to make economic enquiries possible. Ultimately, by this view we reconcile morality with value neutrality in economics, without slicing the discipline into two distinctive branches.